Feedback system for automatic fish feeder - Ahmad Zulkhairi Mohd. Khalid, 1987- , author; Zulkifli Md Yusof, supervisor; Azli Yahya, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Includes bibliographical references